Upaya Meningkatkan Hasil Belajar Matematika Siswa melalui Model Pembelajaran Problem Based Learning (PBL) terhadap Siswa Kelas VII SMPN 3 Boronadu - Yusueli Hulu (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
The purpose of this study was to improve students' mathematics learning outcomes through Problem Based Learning (PBL)for students of VII SMPN 3 Boronadu. This research is classroom action research with several stages of research, namely planning (plan), action (act), observation (observe) and reflection (reflect). This research was conducted at in the acade SMP Kelas VII SMPN 3 Boronadu mic year 2021/2022. The research subjects were class VII students of SMPN 3 Boronadu, totaling 21 students. The instruments used were observation sheets on the implementation of learning, tests of student learning outcomes. The data analysis technique is to calculate the average value of observations by categorizing the level of student learning outcomes. The results showed that the Problem Based Learning (PBL) could improve the learning outcomes of class VII students of SMPN 3 Boronadu The research data obtained from cycle I and cycle II illustrate that there is an increase in student learning outcomes. This is evident from the first cycle the number of students who completed as many as 13 people increased in the second cycle to 16 people. The percentage of class completeness in the first cycle was 61.90%, an increase of 14.28% to 76.19% in the second cycle.